WOMEN AND PARLIAMENT (Political Sociological Analysis of Women's Strategies for Legislative Parliament Election in Central Sulawesi for the Period 2019-2024) - abdul kadir Patta; Hesti Astuti; Ritha Safithri; Abdul Rivai; Moh. Nutfa (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study was aimed to find the position, composition and strategy of women's electability in members of the Central Sulawesi legislature in period 2019-2024. The method that used of this study was qualitative with descriptive type. Data collection were obtained by observation, interviews and documentation of primary and secondary data. The results showed that the representation of women in the Central Sulawesi legislature was increased about 34% from the previous 2009-2014. Women occupying 12 seats of 45 seats and getting an additional 1 seat from the Intermediate Substitute. Even in the placement of, women occupy strategic positions. Women who become members of parliament have their own strategies to be able to fight for the most votes.